Changes in oral, skin, and gut microbiota in children with atopic dermatitis: a case-control study - Zhang, Xueer; Huang, Xiaomin; Zheng, Pai; Liu, E.; Bai, Sixian; Chen, Shuoyu; Pang, Yaobin; Xiao, Xinyu; Yang, Huifang; Guo, Jing (Frontiers in Microbiology, 2024)
Atopic dermatitis (AD) is a common clinical recurrent atopic disease in dermatology, most seen in children and adolescents. To explore the synergistic effects between colonizing bacteria from different sites and AD, we comparatively analyzed the skin, oral, and gut microbiota of children with AD (50 individuals) and healthy children (50 individuals) by 16S rRNA gene sequencing. Twenty samples were also randomly selected from both groups for metabolic and macrogenomic sequencing. The results of our sequencing study showed reduced microbiota diversity in the oral, skin, and gut of children with AD (P<0.05). Metabolomics analysis showed that serotonergic synapse, arachidonic acid metabolism, and steroid biosynthesis were downregulated at all three loci in the oral, skin, and gut of children with AD (P<0.05). Macrogenomic sequencing analysis showed that KEGG functional pathways of the three-site flora were involved in oxidative phosphorylation, ubiquitin-mediated proteolysis, mRNA surveillance pathway, ribosome biogenesis in eukaryotes, proteasome, basal transcription factors, peroxisome, MAPK signaling pathway, mitophagy, fatty acid elongation and so on (P<0.05). The combined microbial, metabolic, and macrogenetic analyses identified key bacteria, metabolites, and pathogenic pathways that may be associated with AD development. We provide a more comprehensive perspective and in-depth understanding of the role of microbiota at different sites in AD patients.